Aquaculturists preference heterogeneity towards wetland ecosystem services : a latent class discrete choice model - Roseliza Mat Alipiah,; Zuraini Anang,; Noorhaslinda Kulub Abdul Rashid,; Smart, James C. R.; Wan Noorwatie Wan Ibrahim, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The fundamental objective of discrete Choice Experiments (CEs) model or Choice Modelling (CM) is to understand the behavioural processes among individuals which drive the choice decisions based on selected attributes and choice options. Preferences may differ among individuals triggered by their specific characteristics such as sociodemographics, constraints and attitudes. Preferences could also vary among groups and within a particular group by forming different segments of groups or subgroups. The Latent Class (LC) model is a distinctive approach which can accommodate preference heterogeneity where preferences are assumed to be relatively homogenous within the segments, but substantially different between the segments. This LC model was applied to account for preference heterogeneity among aquaculturists in the Setiu Wetlands, Terengganu. Currently, fish cage culture is the main socio-economic activity which imposes considerable impacts on the wetland ecosystem and thus affect its ability to deliver ecosystem service outcomes to other stakeholder groups. This research quantifies the aquaculturists’ preferences heterogeneity with regard to the ecosystem impacts under different management scenarios. The existence of sub-divisions of preferences within the stakeholder subgroups was tested. This study revealed three latent classes or segments which show relatively distinct sets of preferences. Segment 1 shows a strong preference for higher harvest rates, a moderately strong preference for higher fisheries income and a moderately strong preference for lower shellfish collections. Segment 2 shows a moderately strong linear preference for higher harvest rates and a very strong preference for retaining the status quo. Segment 3 shows a perplexing set of significant preferences for increasing harvest rates and a modest preference for higher fisheries income. In direct contrast to Segment 2, Segment 3 shows a very strong aversion to retaining the status quo. The results of aquaculturists’ preferences for delivery of different ecosystem services in Setiu Wetlands suggest that Latent Class Model (LCM) could be applied successfully in a Malaysian setting. The success of the LC model is evidenced by the high level of fit obtained from the best fitting models. The main finding of this research suggests that a good understanding of the main research objective, familiarity with the research area and carefully designed choice set, as well as employing appropriately trained enumerators are the main factors that particularly contribute to a successful application of the LC model in a developing country setting.